Economic dynamics : phase diagrams and their economic application - Shone, Ronald (Cambridge ; New York : Cambridge University Press, 1997)
The book provides a long-awaited, up-to-date and thorough introduction to dynamics and phase diagrams and their economic application. It covers both quantitative and qualitative dynamic systems; continuous and discrete dynamics; linear and non-linear systems; and single equations and systems of equations.
Includes bibliographical references: p. (535-540) and index.
rua 13/06/2017
Loans
Keywords: Economics, Mathematical; Phase diagrams; Statics and dynamics (Social sciences).